Assessing Idaho Rural Family Physician Scope of Practice Over Time. Issue 3 (1st February 2015) - Schmitz, David; Baker, Ed; MacKenzie, Lisa; Kinney, Logan; Epperly, Ted
Abstract Context An important consideration determining health outcomes is to have an adequate supply of physicians to address the health needs of the community. Purpose The purpose of this investigation was to assess scope of practice factors for Idaho rural family physicians in 2012 and to compare these results to findings from a 2007 study. Methods The target population in this study was rural family physicians in Idaho counties with populations of fewer than 50, 000. Identical surveys and methods were utilized in both 2007 and 2012. Results The physician survey was mailed to 252 rural physicians and was returned by 89 for a response rate of 35.3%. Parametric and nonparametric statistical analyses were conducted to analyze the 2012 results and to assess changes in scope of practice across the time periods. Discussion The percentage of rural family physicians in Idaho in 2012 who provided prenatal care, vaginal deliveries, and nursing home care was significantly lower than the results from the 2007 survey. Female physicians were more likely to provide prenatal care and vaginal deliveries than males in 2012. Male physicians were more likely to provide emergency room coverage and esophagogastroduodenoscopy or colonoscopy services than females in 2012. Younger physicians were found to be more likely to provide inpatient admissions and mental health services in 2012 than older physicians. Employed physicians were more likely to provide cesarean delivery, other operating room services and emergency room coverage in 2012 than nonemployed physicians. Further research is needed to assess the root causes of these changes.